2003
DOI: 10.4049/jimmunol.170.7.3554
|View full text |Cite
|
Sign up to set email alerts
|

Murine Flt3 Ligand Expands Distinct Dendritic Cells with Both Tolerogenic and Immunogenic Properties

Abstract: Human Flt3 ligand can expand dendritic cells (DC) and enhance immunogenicity in mice. However, little is known about the effects of murine Flt3 ligand (mFlt3L) on mouse DC development and function. We constructed a vector to transiently overexpress mFlt3L in mice. After a single treatment, up to 44% of splenocytes became CD11c+ and the total number of DC increased 100-fold. DC expansion effects lasted for >35 days. mFlt3L DC were both phenotypically and functionally distinct. They had increased expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
56
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 46 publications
9
56
0
1
Order By: Relevance
“…1A). Our results are consistent with studies with psoralen-UV-inactivated recombinant Ad (31,32), where transcriptionally inactive viral templates were found to induce BMDC maturation as efficiently as unmodified virus. Therefore, BMDC maturation in response to Ad exposure does not depend on efficient gene expression associated with the high affinity uptake pathway known to function with CAR-containing cell lines.…”
Section: Autocrine Activation Of Bmdc Through Ad-induced Tnf-␣ Secretsupporting
confidence: 81%
“…1A). Our results are consistent with studies with psoralen-UV-inactivated recombinant Ad (31,32), where transcriptionally inactive viral templates were found to induce BMDC maturation as efficiently as unmodified virus. Therefore, BMDC maturation in response to Ad exposure does not depend on efficient gene expression associated with the high affinity uptake pathway known to function with CAR-containing cell lines.…”
Section: Autocrine Activation Of Bmdc Through Ad-induced Tnf-␣ Secretsupporting
confidence: 81%
“…Previous reports suggested the risk that systemically administered FLT3L could induce immunotolerance in vivo by increasing immature DCs (17)(18)(19)(20)(21), although others reported contrary findings (4,15). These conflicting data suggest that FLT3L may give rise to immunotolerance if administered systemically, and the enhancement of tumor immunity mainly depends on the circumstances where local immune response is evoked.…”
Section: Discussionmentioning
confidence: 45%
“…Instead, accelerated tumor growth occurred after challenge with a tumor expressing the relevant peptide. 24 These, as well as other studies, have suggested that Flt3L, like other cytokines, 25 can stimulate the expansion of immature myeloid suppressor cells (IMSCs). These cells have the potential to promote tumor escape from immune control by inhibiting adaptive immune responses, DC function, and infiltration of tumors with T cells, resulting in the suppression of T-cell control of tumor progression and growth.…”
mentioning
confidence: 99%
“…20 Flt3L has been reported to exhibit a paradoxical profile; in some cases, it has been found to expand DCs in the absence of a therapeutic response and to induce tolerance. 24 Furthermore, in some studies when adenovirus-(Adv-) Flt3L-expanded DCs were loaded with tumor peptides and used as a vaccine, no protection was observed. Instead, accelerated tumor growth occurred after challenge with a tumor expressing the relevant peptide.…”
mentioning
confidence: 99%